2002
DOI: 10.1152/ajpgi.00238.2001
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of fatty acids between intracellular membranes: roles of soluble binding proteins, distance, and time

Abstract: Soluble fatty acid binding proteins (FABPs) are thought to facilitate exchange of fatty acids between intracellular membranes. Although many FABP variants have been described, they fall into two general classes. "Membrane-active" FABPs exchange fatty acids with membranes during transient collisions with the membrane surface, whereas "membrane-inactive" FABPs do not. We used modeling of fatty acid transport between two planar membranes to examine the hypothesis that these two classes catalyze different steps in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
17
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 41 publications
3
17
0
1
Order By: Relevance
“…Luxon (24) showed that the cytoplasmic transport of 12-N-methyl-7-nitrobenzo-2-oxa-1,3-diazol-amino stearate is modulated by binding to soluble proteins like FABPs and that FABPs enhance diffusive transport by reducing binding to immobile cytosolic membranes. Weisiger and Zucker (42) have recently proposed a simple kinetic model for cytoplasmic diffusion and suggested that "membrane-active" FABPs are the soluble fatty acid binding proteins that enhance faster cytoplasmic diffusion of fatty acids. The correlation between PS for unchanged [ 3 H]palmitate and the L-FABP level (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Luxon (24) showed that the cytoplasmic transport of 12-N-methyl-7-nitrobenzo-2-oxa-1,3-diazol-amino stearate is modulated by binding to soluble proteins like FABPs and that FABPs enhance diffusive transport by reducing binding to immobile cytosolic membranes. Weisiger and Zucker (42) have recently proposed a simple kinetic model for cytoplasmic diffusion and suggested that "membrane-active" FABPs are the soluble fatty acid binding proteins that enhance faster cytoplasmic diffusion of fatty acids. The correlation between PS for unchanged [ 3 H]palmitate and the L-FABP level (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Luxon and co-workers (18) reported that 1) increasing the cytosolic concentration of L-FABP caused a parallel increase in the rate of cytoplasmic palmitate transport in clofibrate-treated male rats; and 2) whereas higher levels of membrane transporters may explain the increased rates of influx and efflux in clofibrate-treated male rats, L-FABP could also directly catalyze transfer of fatty acids to and from the inner surface of the plasma membrane through a collisional mechanism. Weisiger and Zucker (35) have recently proposed a simple kinetic model for cytoplasmic diffusion and suggested that "membrane-active" FABPs are the soluble FABP that enhance faster cytoplasmic diffusion of fatty acids. However, hepatic extraction of palmitate and other solutes may also be influenced by the albumin contents in the perfusate, perfusion flow rate, and vascular dispersion (28,34).…”
Section: Ajp-gastrointest Liver Physiolmentioning
confidence: 99%
“…This monograph addresses the transport functions of FABPs in intuitive terms. This topic has been addressed in more detail previously, and the reader is referred to these papers for a more comprehensive discussion (Weisiger 1998(Weisiger , 1999(Weisiger , 2002Weisiger and Zucker 2002).…”
mentioning
confidence: 99%
“…Because the fatty acid never enters the water phase, this process requires much less energy and thus happens much more quickly. FABPs that have the ability to catalyze dissociation from membranes have been termed "membrane active," whereas those that lack this ability are "membrane inactive" (Weisiger and Zucker 2002). Liver FABP appears to be membrane inactive, whereas all other FABPs that have been studied for this ability seem to have the ability to catalyze dissociation.…”
mentioning
confidence: 99%
See 1 more Smart Citation